2007
DOI: 10.3168/jds.2006-827
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability of Lactoferrin Content Estimated by Mid-Infrared Spectrometry in Bovine Milk

Abstract: The effects of lactoferrin (LF) on the immune system have already been shown by many studies. Unfortunately, the current methods used to measure LF levels in milk do not permit the study of the genetic variability of lactoferrin or the performance of routine genetic evaluations. The first aim of this research was to derive a calibration equation permitting the prediction of LF in milk by mid-infrared spectrometry (MIR). The calibration with partial least squares on 69 samples showed a ratio of standard error o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
44
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 23 publications
8
44
2
1
Order By: Relevance
“…As it is possible to determine the total content of protein and some specific milk proteins, it could be possible to predict the LTF content of milk using MIR as LTF is a natural milk glycoprotein. This hypothesis was tested by Soyeurt et al (2007) who suggested the possibility of quantification of an indicator of LTF in bovine milk using MIR spectrometry with a cross-validation coefficient of determination (R 2 CV ) of 0.75. However, the study of Soyeurt et al (2007) had several limitations; only 69 samples collected in the Walloon region of Belgium were used to develop the equation through a partial least squares regression (PLS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it is possible to determine the total content of protein and some specific milk proteins, it could be possible to predict the LTF content of milk using MIR as LTF is a natural milk glycoprotein. This hypothesis was tested by Soyeurt et al (2007) who suggested the possibility of quantification of an indicator of LTF in bovine milk using MIR spectrometry with a cross-validation coefficient of determination (R 2 CV ) of 0.75. However, the study of Soyeurt et al (2007) had several limitations; only 69 samples collected in the Walloon region of Belgium were used to develop the equation through a partial least squares regression (PLS).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was tested by Soyeurt et al (2007) who suggested the possibility of quantification of an indicator of LTF in bovine milk using MIR spectrometry with a cross-validation coefficient of determination (R 2 CV ) of 0.75. However, the study of Soyeurt et al (2007) had several limitations; only 69 samples collected in the Walloon region of Belgium were used to develop the equation through a partial least squares regression (PLS). Recent studies to predict other components in milk have shown a benefit in the accuracy of calibration equations with (1) more complex calibration procedures, (2) a larger number of samples from a wider range of production systems and (3) greater animal diversity (Dal Zotto et al, 2008;Soyeurt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The low LTF concentration during the first 2 months of lactation and the highest during the last 3 months could be explained by the dilution effect observed by Arnould et al (2009) and Soyeurt et al (2007) who obtained a negative genetic correlation between daily milk production and LTF content of -0.25 and -0.36, respectively. A significant increase in LTF concentration in the following stages of lactation was in agreement with the results obtained by other authors (Hagiwara et al 2003, Cheng et al 2008a.…”
Section: Discussionmentioning
confidence: 99%
“…This observation confirms the previous conclusions of many reports showing the increase in lactoferrin content in milk from infected udders compared with healthy cows (Kawai et al 1999, Hagiwara et al 2003, Cheng et al 2008b, Arnould et al 2009). LTF level in milk is believed to be a good indicator of mastitis because of a high positive correlation between LTF and SCC (Lindmark-Mansson 2006, Soyeurt et al 2007, Arnould et al 2009) and is also useful in detecting the false-positive results of screening tests for antibiotic residues in milk (Malinowski et al 2008). Cheng et al (2008b) observed a significant positive correlation of lactoferrin concentrations between serum and milk in early phase of the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraging results, although less accurate, were also obtained in the prediction of individual proteins (e.g. lactoferrin, Soyeurt et al, 2007b) or minerals (Soyeurt et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%